Coverage of the Neurovascular Unit of the Fingertip Using a Reverse Homodigital Dorsal Flap. (9th January 2014) - Perrotta, Rosario E.; Stivala, Alessio; Virzì, Dario; Grella, Roberto; Pagliara, Domenico; Brongo, Sergio
Abstract : The exposure of bone, tendons, vessels, and nerves in a digital defect is one of the most frequent and severe problems to solve in hand surgery and current approaches are still disappointing. We show the use of an homodigital adipofascial flap taken from the same finger for covering the pulpar defect in a one-step surgical technique able to preserve the digital artery.